The Relationship between Customer Value and Trust in Consumer Satisfaction and its Impact on Consumer Loyalty - Yayang Ayu Nuraeni; Arman Maulana (International Journal of Science Education and Technology Management, 2022)
The purpose of this study was to determine the relationship between customer value and trust on consumer satisfaction and its impact on consumer loyalty to consumers of spare parts for heavy equipment excavators at CV. Bandung Jaya Diesel City of Bandung. This research was conducted by taking a sample of 100 consumers. For data analysis using SPSS 20 and AMOST version 21 programs. The results of this study show 1) Customer Value has a significant positive effect on Consumer Satisfaction, 2) Customer Trust has a positive and insignificant effect on Consumer Satisfaction, 3) Service Quality has a significant positive effect on Consumer Loyalty , 4) Customer Trust has a significant positive effect on Consumer Loyalty, 5) Customer Satisfaction has a significant positive effect on Customer Loyalty.